2011
DOI: 10.1056/nejmoa0911353
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Association betweenGLCCI1and Response to Glucocorticoid Therapy in Asthma

Abstract: BACKGROUND The response to treatment for asthma is characterized by wide interindividual variability, with a significant number of patients who have no response. We hypothesized that a genomewide association study would reveal novel pharmacogenetic determinants of the response to inhaled glucocorticoids. METHODS We analyzed a small number of statistically powerful variants selected on the basis of a family-based screening algorithm from among 534,290 single-nucleotide polymorphisms (SNPs) to determine change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
301
4
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(324 citation statements)
references
References 37 publications
8
301
4
11
Order By: Relevance
“…Factors associated with a diminished dose response to ICSs include genetic polymorphisms, COPD, smoking, severe asthma, obesity, and vitamin D insufficiency (8,(19)(20)(21)(22). Patients with asthma who are homozygous for the variant allele rs37973, which maps to the glucocorticoid-induced transcript 1 gene (GLCCI1), show about one third the lung function response of that of those homozygous for the wild-type allele (19).…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with a diminished dose response to ICSs include genetic polymorphisms, COPD, smoking, severe asthma, obesity, and vitamin D insufficiency (8,(19)(20)(21)(22). Patients with asthma who are homozygous for the variant allele rs37973, which maps to the glucocorticoid-induced transcript 1 gene (GLCCI1), show about one third the lung function response of that of those homozygous for the wild-type allele (19).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Patients with asthma who are homozygous for the variant allele rs37973, which maps to the glucocorticoid-induced transcript 1 gene (GLCCI1), show about one third the lung function response of that of those homozygous for the wild-type allele (19). The variant occurs in about 16% of the population.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Six GWAS studies reported genetic variants to be associated with treatment response [30][31][32][33][34][35], while a large recent GWAS did not find any significantly associated genetic variants [36]. The GWAS that did identify genetic variants to be associated with ICS response, all reported different genes to be most significantly associated with response to ICS.…”
Section: Ics Responsementioning
confidence: 99%
“…The first GWAS on ICS response was published in 2011 by Tantisira and coworkers. They studied 118 child-parent trios included in the Childhood Asthma Management Program (CAMP), a multicenter RCT trial (discovery phase) and subsequently aimed to replicate identified variants in 935 asthmatic adults and children from four different replication populations [31]. Variation in the GLCCI1 gene, encoding the …”
Section: Ics Responsementioning
confidence: 99%
“…In this context, the reduced effectiveness of inhaled glucocorticoids is an important challenge. It seems to be partly associated with a polymorphism in the glucocorticoid-induced transcript 1 gene (44). Even more prominent may be the effect of differences in phenotypes; patient groups with high symptom levels but low eosinophilic inflammation seem to have only moderate benefit from inhaled glucocorticoids (3).…”
Section: Many Different Phenotypes?mentioning
confidence: 99%